In silico profiling of neem limonoids and gut microbiome metabolites for Alzheimer’s therapeutics: targeted inhibition of BACE1 and elucidation of intricate molecular crosstalk with tau oligomers, and bacterial gingipains - Agboola, Oluwaseun E.; Ayinla, Zainab A.; Agboola, Samuel S.; Omolayo, Esther Y.; Fadugba, Abimbola E.; Odeghe, Othuke B.; Olaiya, Oluranti E.; Oyinloye, Babatunji E. (Discover applied sciences, 2025)
Alzheimer’s disease (AD) is characterized by the accumulation of amyloid beta plaques and neurofibrillary tangles composed of hyperphosphorylated tau protein. This study computationally investigated natural neem compounds (limonoids) and gut microbiome metabolites for their inhibitory potential against key AD targets. Molecular docking analyses were performed on approximately 200 neem phytochemicals and 9 microbial metabolites against beta-secretase 1 (BACE1), gingipain cysteine protease, and tau oligomerization receptors using AutoDock. BBB permeability was computationally evaluated using six molecular descriptors: molecular weight, LogP, hydrogen bond acceptors/donors, polar surface area, and rotatable bonds, categorizing compounds as highly or poorly BBB permeable based on established predictive criteria. The results revealed superior binding affinities of limonoids, notably Rutin (− 9.642 kcal/mol), 7-benzoylnimbocinol (− 9.706 kcal/mol), and tirucallol (− 9.488 kcal/mol) against BACE1, gingipain protease, and tau oligomerization receptors, respectively. These compounds exhibited key interactions through hydrogen bonding with Gly34, Asn233 (rutin-BACE1), Lys311, and Asn363 (7-benzoylnimbocinol-gingipain) and hydrophobic interactions with Ile40 and Ile48 (tirucallol-tau). While these limonoids demonstrated binding affinities exceeding melatonin by > 30%, their BBB permeability profiles necessitate sophisticated delivery strategies. Among gut microbiome metabolites, melatonin showed consistent binding across all targets (− 7.079 to − 8.452 kcal/mol). These findings establish limonoids’ superiority over gut microbiome metabolites and highlight their therapeutic potential as multi-target inhibitors in AD pathology, warranting investment in nanocarrier systems for optimizing BBB penetration. Article Highlights In silico, screening identified neem phytochemicals as potent inhibitors of key Alzheimer's disease targets, exhibiting superior binding affinities compared to gut microbiome metabolites. Compounds like rutin, nimbolin B, and protolimonoids demonstrated remarkable docking scores against the BACE1 enzyme, a crucial therapeutic target in the amyloidogenic pathway. Indole melatonin consistently displays robust interactions across BACE1, gingipain protease, and tau protein receptors, highlighting its potential as a privileged scaffold for Alzheimer’s drug development.